2002
DOI: 10.1161/01.cir.0000018124.01299.ae
|View full text |Cite
|
Sign up to set email alerts
|

Conversion From Vagal to Sympathetic Predominance With Strenuous Training in High-Performance World Class Athletes

Abstract: Background-Benefits of moderate endurance training include increases in parasympathetic activity and baroreflex sensitivity (BRS) and a relative decrease in sympathetic tone. However, the effect of very intensive training load on neural cardiovascular regulation is not known. We tested the hypothesis that strenuous endurance training, like in high-performance athletes, would enhance sympathetic activation and reduce vagal inhibition. Methods and Results-We studied the entire Italian junior national team of row… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
248
1
16

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 266 publications
(289 citation statements)
references
References 42 publications
24
248
1
16
Order By: Relevance
“…[17][18][19] Spectral analysis of respiratory activity was performed only to assess the main respiratory frequency. [17][18][19] Two main components were considered in the RRI and SBP variability signals: that in the frequency band from 0.04 to 0.15 Hz (low-frequency [LF]) and that in the range from 0.15 to 0.4 Hz (high-frequency [HF]). The power density of each spectral component was calculated in absolute values and normalized units (nu).…”
Section: Power Spectral Analysismentioning
confidence: 99%
“…[17][18][19] Spectral analysis of respiratory activity was performed only to assess the main respiratory frequency. [17][18][19] Two main components were considered in the RRI and SBP variability signals: that in the frequency band from 0.04 to 0.15 Hz (low-frequency [LF]) and that in the range from 0.15 to 0.4 Hz (high-frequency [HF]). The power density of each spectral component was calculated in absolute values and normalized units (nu).…”
Section: Power Spectral Analysismentioning
confidence: 99%
“…1,2,3 However, quantitative studies on the beneficial effects of endurance training on visceral nerves are scarce and these studies are referred especially to functional aspects of the nerves rather than the morphological or quantitative aspects. [4][5][6][7][8] Goldsmith et al 4 and Iellano et al 5 demonstrated that moderate endurance exercise increases the vagal tonus and diminishes the action of the sympathetic nerve, protecting the heart.…”
Section: Introductionmentioning
confidence: 99%
“…Quanto à hipótese da VFC não ter se alterado devido à pequena magnitude no aumento das cargas de treinamento em T1, em estudos nos quais houve aumentos consideráveis das cargas de treinamento, da ordem de até 100% do total treinado 13,14 , foram observadas mudanças significativas na VFC. Contudo, estudos recentes em que as alterações das cargas de treinamento não foram tão grandes, não encontraram alterações na VFC após períodos com cargas de treinamento diferentes, moderadas e altas ao longo da temporada esportiva 16,17 .…”
Section: Estresse Geralunclassified
“…Sendo assim, mudanças na modulação autonômica cardíaca aparentemente são percebidas apenas em situações em que atletas são submetidos a cargas de treinamento extremamente elevadas, de forma a levar os voluntários à exaustão 9,15 , o que nem sempre ocorre numa situação real de treinamento com finalidade competitiva, como nesta investigação, na qual o programa de treinamento foi concebido visando a participação em competição de nível nacional, e, não, no intuito de levar os voluntários a situações extremas de fadiga crônica. Outros estudos mostram, ainda, que ocorrem modificações na atuação simpática apenas em períodos curtos de tempo como adaptação ao treinamento, imediatamente seguintes às alterações na carga de exercícios 13,14,17 . No presente estudo as coletas foram realizadas em intervalos de quatro Tabela 1.…”
Section: Estresse Geralunclassified
See 1 more Smart Citation